PEMISAHAN DAN KARAKTERISASI EMULSIFIER DALAM MINYAK CACING TANAH (Lumbricus rubellus) - Muhammad Zein Nasution, Ani Suryani dan Irma Susanti (Department of Agroindustrial Technology, Bogor Agricultural University, 2004)
ABSTRACTEmulsifier in earthworm oil is expected as phospholipid. It is produced from degumming process by the variation of phosphoric acid and citric acid added 0,1% v/w and 0,2% v/w. The highest yield of gum was produced by adding 0,2% v/w of acid. The characteristic of emulsifier such as reducing surface tension, surface tension of two phase, and maintaining the emulsion stability are not different for gum and degummed earthworm oil by acid degumming. Gum by acid degumming is not different from gum water degumming and undegumming earthworm oil in its ability to reduce surface tension and surface tension of two phase. Earthworm oil by acid degumming is not different from earthworm oil by water degumming and undegumming earthworm oil in ability to reduce surface tension and surface tension of two phase. Generally, the ability of undegummed earthworm oil to maintain the emulsion stability is better than gum and degummed earthworm oil by acid and water degumming.